ENTERPRISE ARCHITECTURE PLANNING USING TOGAF ADM FOR FUEL DISTRIBUTION OPERATIONS - Putri Kaneshia Rahmadina; Nining Ariati; Agustina Heryati (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
PT Dian Aristy Energi Palembang is a company engaged in the distribution of industrial fuel oil (BBM). The current operational processes are still conducted manually and are not integrated, leading to data duplication, reporting delays, low information accuracy, and difficulties in monitoring distribution activities, which affect managerial decision-making. This study aims to develop a strategic Enterprise Architecture plan based on TOGAF ADM to improve the alignment between information systems and fuel distribution operations. The research method used is qualitative descriptive with a case study approach, with data collection techniques including interviews, observations, and documentation. The TOGAF ADM phases applied consist of Preliminary Phase, Architecture Vision, Business Architecture, Information System Architecture, and Technology Architecture. The results of this study produce an Enterprise Architecture design that describes the current condition (AS-IS) and the proposed condition (TO-BE), including business process modeling, data architecture, application architecture, and supporting technology architecture. The proposed design enables the integration of operational processes through digital systems such as purchase order processing, distribution monitoring, and complaint management. This study concludes that the implementation of Enterprise Architecture based on TOGAF ADM can improve operational efficiency, data accuracy, information transparency, and support better decision-making, as well as provide a reference for the development of integrated information systems